2015
DOI: 10.1097/brs.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

The Spine Surgical Care and Outcomes Assessment Program (Spine SCOAP)

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The impact of baseline functional status on postoperative outcomes following lumbar spine surgery is a consistent finding in the literature. 11,12,19,28,[36][37][38]44,46,48,65 Analogous to our results, numerous previous studies have demonstrated that the patients whose baseline disability, pain, and QOL scores are, on average, worse than those of others are more likely to have poorer outcomes at 12 months. 3,14,48 Conversely, we found that patients with higher baseline NRS-LP scores had greater odds of having better outcomes.…”
Section: Predictors Of Outcomesupporting
confidence: 85%
“…The impact of baseline functional status on postoperative outcomes following lumbar spine surgery is a consistent finding in the literature. 11,12,19,28,[36][37][38]44,46,48,65 Analogous to our results, numerous previous studies have demonstrated that the patients whose baseline disability, pain, and QOL scores are, on average, worse than those of others are more likely to have poorer outcomes at 12 months. 3,14,48 Conversely, we found that patients with higher baseline NRS-LP scores had greater odds of having better outcomes.…”
Section: Predictors Of Outcomesupporting
confidence: 85%
“…A team of experts from four leading orthopedic registries that collect PROMs (FORCE-TJR, CERTAIN, the Kaiser Permanente Total Joint Registry and the California Joint Replacement Registry) [19202122], together with diverse stakeholders (clinicians, patients, electronic medical record vendors, hospital administrators, health services and outcomes researchers, and policymakers), identified generalizable PROM implementation lessons. These lessons informed a framework and toolkit of promising strategies to accelerate collection and use of PROMs in health care.…”
Section: Methodsmentioning
confidence: 99%
“…Many Washington State hospitals participate in a novel data surveillance and benchmarking network called the Spine Surgical Care and Outcomes Assessment Program (Spine SCOAP), a quality improvement and benchmarking collaborative [20]. Participation in Spine SCOAP is voluntary, but approximately 75% of eligible spinal procedures in Washington State take place within the Spine SCOAP network.…”
Section: Methodsmentioning
confidence: 99%